CONSUMPTION OF FRESH AND MINIMALLY PROCESSED FOODS IN A REFERENCE CENTER IN SERRA GAUCHA - Longoni, Bruna; Queiroz Caberlon, Vitória; Zortéa, Juliana; Assoni Bilibio, Sarah; de Oliveira Pereira Vergani, Daiane; Antoniazzi dos Santos, Pâmela (Health and Society, 2023)
Objective: To evaluate the average daily consumption of fresh and minimally processed foods in high -risk pregnant women. METHODOLOGY: A cross -sectional, with 51 high -risk pregnant women attended at a high -risk pregnancy center in Caxias do Sul –RS. First a food frequency questionnaire was applied and later the demographic and anthropometry data were removed from the pregnant women’s record. It was carried out through the program: Statistical Package for the Social Sciences - SPSS®. Results: The age of pregnant women was predominantly over 30 (55.8), 57.7% had a partner, 71%, white race and 48.1% of participants had over 8 years of study. As for nutritional status, 55.8% of participants had excess weight, 7.7% with fasting glucose ≥126mg/dL. There was a significant association between higher consumption of fresh and minimally processed foods among married (19.07) when compared to non-married (15.3) (p = 0.011). CONCLUSION: The consumption of fresh and minimally processed foods of the pregnant women studied in general showed a relatively high intake. The influence of socio-economic factors on food consumption reported in the literature has identified that married and more years of study, favor healthier eating habits.